Good Teaching Practices in Education and Support to Learning in Middle School - Llangari , Jackeline Daysi Chiqui; Correa , Ximena Patricia Curay; Simbaña , Christian Rafael Quimbiulco; Porras , Edison Bladimir Charro (Journal of Ecohumanism, 2024)
Contemporary education faces the challenge of innovating to improve the quality of learning, requiring teachers to adopt effective methodological strategies. This study examines teaching strategies and good practices in middle school education in Cuenca, Ecuador, with the objective of identifying effective approaches and areas for improvement. The methodology employed was mixed, combining qualitative and quantitative approaches. A prospective and non-experimental design was used, which allowed observing educational phenomena without intervening in their development. The research included semi-structured interviews, focus groups and life stories to capture in-depth educational experiences. In addition, surveys were applied to a representative sample of teachers and students to obtain quantitative data on the perception and effectiveness of teaching practices. The main result of the study highlights that solid teacher training and the use of innovative technologies are crucial to improve educational quality and promote an inclusive and equitable environment.